Nonlinear Fokker-Planck Equation in the Model of Asset Returns; Symmetry, Integrability and Geometry: Methods and Applications (SIGMA); Vol. 4 - Shapovalov A. V. Aleksandr Vasilyevich (2008, 2008)
Title screen